Teaching Arabic as a Foreign Language : Origins, Developments and Current Directions - Facchin, Andrea (Book collections on Project MUSE., 2019)
*Teaching Arabic as a Foreign Language* concentrates on the origins, developments and current directions of the discipline Teaching Arabic as a Foreign Language (TAFL) within the Arab world and partially outside of it during the last 60 years, namely between 1958 and 2018. Considered in this volume are the most influential scholars, authors, educators and those significant works that have contributed to the development of the discipline. In addition, special attention is paid to the TAFL institutes, regarded as epicenters of TAFL activities and important meetings, that allow scholars to gather around the same table and discuss approaches, trends and methods used in the field. All of these aspects converge in one comprehensive study which is enriched by a narration of the main sociopolitical changes that have affected the Middle East in latter-day history.